Development of creative thinking patterns via math and music. (March 2023) - Azaryahu, Libby; Broza, Orit; Cohen, Shai; Hershkovitz, Sara; Adi-Japha, Esther
Highlights: This MusiMath study assessed the development of patterns' creative thinking. Three 3rd grade classes emphasizing creative math/music/math-and-music participated. Control and experimental classes answered open and closed math and music questions. Experimental groups outperformed the control group on patterns' creative thinking. Abstract: The present study examines the development of patterns of creative thinking among third graders ( N = 84) following multidisciplinary learning that combines math and music with various teaching emphases. For the purpose of the study, an intervention program was used focusing on patterns of creative thinking. Three classes received identical MusiMath instruction that explicitly links math and music. These classes received additional instruction regarding patterns of creative thinking differing in focus: Creative Math class, Creative Music class, and Creative Math and Music class. The fourth class was used as a control class that learned math and music in a standard way without creative intervention. To collect the data, we developed software that enabled the students to perform musical and mathematical tasks that included questions with only one correct answer, and questions that invited original and varied answers that encouraged creative thinking. Pre‐ to post‐intervention analyses indicated that the experimental groups outperformed the control group on patterns of creative thinking in both math and music, regardless of the teaching focus. Combined instruction in creativity in the Math and Music class resulted in similar patterns of creativity in the two domains, suggesting that the creative thinking was transferable from one domain to another.